Quantitative leachate estimation from a pilot-scale lysimeter study. (24th July 2009) - Manandhar, Dinesh Raj; Krishnamurthy, V.; Kasaju, Yamuna Shanker
Sanitary landfilling is the most important component of waste management. One of the main concerns is water contamination by leachate. This paper presents the outcome of the research on the water management of landfill in Nepal. The related leachate production as an effect of climatical factors is assessed. The Hydrologic Evaluation of Landfill Performance (HELP) computer model has been used to compute estimates of water balances. The evaluation as well as applicability of the model has been discussed. The application of the model has raised issue like effect on water balance by the variation of short-term rainfall into percolation.